2014
DOI: 10.1182/blood-2013-11-533406
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular oxygen consumption during sickle cell pain crisis

Abstract: • Patients with sickle cell disease have greater microvascular oxygen consumption rates than healthy individuals.• During sickle cell pain crisis, microvascular oxygen consumption increases further.Sickle cell disease is an inherited blood disorder characterized by chronic hemolytic anemia and episodic vaso-occlusive pain crises. Vaso-occlusion occurs when deoxygenated hemoglobin S polymerizes and erythrocytes sickle and adhere in the microvasculature, a process dependent on the concentration of hemoglobin S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…While blood volume was not explicitly measured by their device, microvascular oxygen consumption was elevated in SCD and further elevated during painful crisis. This is consistent with our finding of a trend towards increased blood volume and oxygen delivery in subcutaneous tissue at painful sites (opposite to our a priori hypothesis) [22]. Blood flow has been explored in SCD using other modalities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While blood volume was not explicitly measured by their device, microvascular oxygen consumption was elevated in SCD and further elevated during painful crisis. This is consistent with our finding of a trend towards increased blood volume and oxygen delivery in subcutaneous tissue at painful sites (opposite to our a priori hypothesis) [22]. Blood flow has been explored in SCD using other modalities.…”
Section: Discussionsupporting
confidence: 91%
“…Certain rheological parameters associated with vaso-occlusion have been found to fluctuate throughout the steady state, with no significant difference in the level of fluctuation between steady state and crisis [21]. Recently, tissue oximetry measurements at the thenar eminence demonstrated that microvascular oxygen consumption is elevated in SCD compared to controls, and further elevated during painful episodes [22]. While some patients demonstrate vaso-occlusion (as shown by an increased percentage of dense cells in the blood) concurrently with the onset of pain, others show similar blood characteristics with no pain [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico studies carried out with quercetin on deoxy-haemoglobin and 2, 3bisphophoglycerate mutase, showed a strong interaction, which was found to effectually bind with the receptors by fully inhabiting their catalytic sites. Higher levels of deoxy-haemoglobin and 2,3-bisphophoglycerate mutase have been reported in SCD (Ngozi, 2013;Poillon et al, 1995;Rowley et al, 2014). Consequently, targeting these proteins via sequestration as 46| This journal is © The Nigerian Young Academy 2019…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms associated with the condition are attributed to a distinct nucleotide alteration in the beta globin gene, which predisposes hemoglobin with the altered amino acid sequence to increased polymerization, microscopically evidenced by red blood cells (RBC) taking a sickle shape (Adewoyin, 2015). This alteration to RBC shape alters not only the structure but also the function of this important protein, resulting in decreased blood flow and lower oxygen supply to tissues and organs (Rowley et al, 2014). Low oxygen levels further cause increased red cell deformation and polymerization which also cause damage to vascular endothelial cells (Sedrak and Kondamudi, 2018).…”
Section: Introductionmentioning
confidence: 99%